Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Umum terhadap Belanja Daerah di Kabupaten Aceh Tamiang - Miranda Ariska; Rizal Yani; Martahadi Mardhani (Jurnal Penelitian Ekonomi Akuntansi, 2022)
This study aims to determine the effect of regional original income and general allocation funds on regional spending in Aceh Tamiang district. This study uses time series data and was obtained from the Central Bureau of Statistics (BPS) of Aceh Tamiang Regency with the 2007-2021 time series. This research model uses multiple linear regression methods using the eviews application. The results of this study indicate that partially Own-Owned Revenue has a positive and significant effect on Regional Expenditure in Aceh Tamiang District, partially General Allocation Fund has a positive and significant effect on Regional Expenditure in Aceh Tamiang District, and simultaneously Regional Original Revenue and General Allocation Fund have an effect positive and significant towards Regional Expenditures in Aceh Tamiang District. The result of the coefficient of determination (R2) is 0.7495 or 74.95% and the remaining 25.05% is influenced by other variables outside this study.regional original income